IDENTIFIKASI DAMPAK PERUBAHAN IKLIM TERHADAP SERI DATA HUJAN DI PULAU JAWA - Adidarma, Wanny Kristyanti (JURNAL SUMBER DAYA AIR, 2018)
The identification of climate change impacts on rainfall (annual, seasonal and monsoon rainfall) was studied using hundreds of rainfall data ranging from 1916-2006. The existence of trend in annual and seasonal rainfall series was detected by Statistical Test, namely Mann-Kendall and the Difference of Two Populations in monsoon series using Mann-Whitney. The results of the test showed that annual and seasonal rainfalls in most of the studied area had decreased where others had increased. The monsoon rainfall showed a significant difference in frequency distribution particularly in the months March-April-May (MAM) and December-January-February (DJF).